Stress Management during the Covid 19 Pandemic: Solutions and Settlement Approaches at Madrasah Aliyah Al-Hidayah, Bandung City - Badrudin -; Zahira Aini Qolby (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2021)
Abstract: The Covid-19 pandemic has an impact on all aspects of life. One of the sectors affected is education. Educational activities that were initially carried out regularly, due to the Covid-19 pandemic all educational activities were carried out online. This change raises various kinds of stress in the educational institution organization. This study aims to explore stress management at MA Al-Hidayah during the Covid 19 pandemic by reviewing its form, settlement strategy and impact. This study uses a qualitative approach with descriptive methods. Data obtained through interviews, observation, and documentation study. The results showed that there were three forms of stress experienced by school principals, teachers, students and parents of students at MA Al-Hidayah during the Covid 19 pandemic, namely stress in the form of frustration, pressure and change. Strategies taken to deal with stress include a) eliminating stressors or stressors, b) controlling the consequences of stress, c) changing individual perceptions of stressors, d) providing moral and social support. While the impact of stress refers to six aspects including a) psychological aspects, b) health aspects, c) performance aspects, d) cognitive aspects, e) emotional aspects and f) behavioral aspects. Abstrak: Pandemi covid-19 berdampak pada seluruh aspek kehidupan. Salah satu sektor yang terdampak adalah pendidikan. Kegiatan pendidikan yang mulanya dilaksanakan secara tetap muka, karena pandemi covid-19 seluruh kegiatan pendidikan dilaksanakan secara online. Perubahan ini memunculkan berbagai macam stress dalam organisasi lembaga pendidikan. Penelitian ini bertujuan untuk mengeksplore manajemen stress di MA Al-Hidayah pada masa pandemi covid 19 dengan meninjau bentuk, strategi penyelesaian, dan dampaknya. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Data diperoleh melalui wawancara, observasi, dan studi dokumentasi. Hasil penelitian menunjukan bahwa terdapat tiga bentuk stress yang dialami oleh kepala sekolah, guru, siswa dan orang tua siswa di MA Al-Hidayah pada masa pandemi covid 19 yaitu stress dalam bentuk frustasi, tekanan, dan perubahan. Strategi yang dilakukan untuk mengatasi stress tersebut di antaranya adalah dengan a) menghilangkan stressor atau pemicu stress, b) mengendalikan konsekuensi stress, c) mengubah persepsi individu terhadap stressor, d) memberikan dukungan moral dan sosial. Sedangkan dampak stress mengacu pada enam aspek di antaranya adalah a) aspek psikologis, b) aspek kesehatan, c) aspek kinerja, d) aspek kognitif, e) aspek emosi dan f) aspek perilaku Kata-kata kunci: Manajemen Stress, Madrasah Aliyah, Pandemi Covid 19